Association between education and self-assessment of the neighborhood environment - Photiou, Galateia; Middleton, Nicos; Panagiotakos, Demosthenes B.; Panayiotou, Andrie G. (My University, 2020)
DEpICT is an ongoing observational, cross-sectional study in community-dwellers in Limassol, Cyprus aiming to combine individual-level and community-level risk factors to decode their effect on arterial health (stiffness) as measured with pulse wave velocity (PWV).
Keywords: Neighborhood socioeconomic assessment; Place Standard; CyNoTes tool; DEpICT; Physical activity; Mediterranean diet; Blood pressure; Cyprus; Decision making; Educational status; Mental health; Ownership; Proxy; Safety; Self assessment; Socioeconomic factors; Quality of life; Arterial stiffness; Community; Family income; General health questionnaire; Neighborhood; Public transportation; Pulse wave velocity; Personally identifiable information